Is the Peripheral Nerve Stimulation the Definitive Solution for Temporomandibular Joint Syndrome? - Alejandra Arévalo-Sáenz; Borja Ferrández-Pujante; Fernando J. Rascón-Ramírez (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Introduction: Temporomandibular joint syndrome is defined by a triad of intense joint pain together with restriction of mouth opening and jaw clicking. It is a syndrome whose prevalence is unknown since it is clearly underestimated. Aim: This study was carried out with the aim of evaluating the efficacy and safety of peripheral nerve stimulation for the treatment of this pathology. The present study highlights peripheral nerve stimulation for the Treatment of Temporomandibular Joint Syndrome (TMJS). Materials and Methods: A retrospective analysis of a series of patients with temporomandibular pain treated by the authors between January 2018 and January 2021 was performed. All patients met selection criteria that included previous resistance to medical or surgical treatment and completion of a series of presurgical tests including a sensitivity test. An octopolar electrode was implanted in the affected preauricular region. The results were measured using different scales including the VAS or Analogue Pain Scale, a short questionnaire on pain, improvement in restriction of mouth opening and reduction of analgesic medication. Results: A total of 10 patients with 14 procedures performed were included. The mean reduction in pain measured by VAS was 86.2% at 1 month and 79% at 1 year after surgery. All patients experienced a dramatic improvement in pain and its impact according to the Brief Pain Inventory, with a mean improvement of 90% at 4 weeks and 82% at 1 year. An improvement in mean oral opening of 10.14 mm (minimum 4 and maximum 13 mm) was observed. One case was excluded due to the complication that required the use of the extraction system. In this study, the treatment is not only peripheral nerve stimulation but also includes transcranial magnetic stimulation as a treatment for this syndrome. Conclusions: Although temporomandibular joint syndrome affects a large population, there is no effective treatment in resistant patients. Peripheral nerve stimulation has proven to be an effective treatment, showing improvement in pain, oral restriction and quality of life with a low percentage of serious complications.